Analysis of Facebook Usage on Increasing Serby Bakery Sales in Sibolangit District - Sembiring, Jenaya Febina; Tarigan, Kesia Septina Putri; Sagala, Tasya Oren; Pasaribu, Raymon P (CV. Rayyan Dwi Bharata, 2025)
In today’s digital era, social media has become an effective marketing tool for various types of businesses, including micro, small, and medium enterprises (MSMEs). Facebook, as one of the largest social media platforms, provides business owners with opportunities to expand their customer reach through interactive and easily accessible promotional strategies. This study aims to analyze the impact of Facebook usage on the sales growth of Serby Bakery in Sibolangit District. The research method used is a qualitative approach, with data collected through direct interviews with MSME owners. The obtained data is then analyzed and structured to examine the relationship between Facebook promotions and sales growth. The study results show that active Facebook usage, paid promotions, and interactive content creation have a significantly positive impact on increasing sales at Serby Bakery. Thus, leveraging social media can be an effective strategy to enhance the competitiveness of bakery businesses in the region.